2020
DOI: 10.1080/14616734.2020.1828531
|View full text |Cite
|
Sign up to set email alerts
|

Observing maternal sensitivity in a South African township: an exploratory study into behavioral features using different measures

Abstract: There is evidence that sensitive responsiveness is manifested differently in varying cultural contexts. This exploratory study examines a sample of 50 South African mothers in the context of a socioeconomically deprived Township, and investigates differences between the Ainsworth sensitivity scale (that does not specify particular manifestations of sensitivity) and the Maternal Behavior Q-sort (MBQ) mini, that assesses a more specified array of behaviors. Results showed a significant but modest association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The current findings on sensitivity are encouraging and correspond with previous studies which have found significant intervention effects on sensitivity in groups of parents who received the ABC versus a control condition (Berlin et al, 2018;Bick and Dozier, 2013;Hepworth et al, 2020;Yarger et al, 2020). Mean sensitivity levels in the present study also meet or exceed the mean AMSS-determined sensitivity recently reported in a sample of South African mothers with typically developing children (Dawson et al, 2021). The parents in the current study were, on average, never-even at baseline-within the insensitive (1-4) range, which also corresponds with the findings of a study by Feniger-Schaal and Joels (2018) among parents of children with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 89%
“…The current findings on sensitivity are encouraging and correspond with previous studies which have found significant intervention effects on sensitivity in groups of parents who received the ABC versus a control condition (Berlin et al, 2018;Bick and Dozier, 2013;Hepworth et al, 2020;Yarger et al, 2020). Mean sensitivity levels in the present study also meet or exceed the mean AMSS-determined sensitivity recently reported in a sample of South African mothers with typically developing children (Dawson et al, 2021). The parents in the current study were, on average, never-even at baseline-within the insensitive (1-4) range, which also corresponds with the findings of a study by Feniger-Schaal and Joels (2018) among parents of children with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 89%
“…Twenty articles reported observational research investigating maternal sensitivity or style within the dyad. Papers reported original research, with the exception of two articles by Judi Mesman (Dawson et al, 2021;Mesman et al, 2021) found in search 1 who re-analysed original articles (Dawson et al, 2018;Mesman, Basweti, et al, 2018) to accommodate newer insights and a recent paper by Mark Tomlinson (Tomlinson et al, 2020) using data from an earlier body of work (Cooper et al, 2002). Numerous measures were used to assess differing components of maternal sensitivity making a meta-analysis for a systematic review impossible.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars of mixed race, indigenous peoples, and activists have long worked on these dimensions and there are powerful examples from which inspiration can be drawn. Similarly, careful assessment and comparison of existing tools 10 can generate important insights about what works best in specific contexts and can also highlight gaps in knowledge, foreground erroneous presumptions (including about the nature of the infant, the context, and the relationship) and enable work that is considerate of history's effects, contextual features, and universal features of infancy and care. 11 As we navigate an exciting and evolving field of what early life and infant mental health and well-being means and how it is represented on the African continent, we encourage the embracing of local scholarly expertise and the addressing of exclusionary scholarly practices.…”
Section: On Not Throwing the Baby Out With The Bathwatermentioning
confidence: 99%